Magnetic Reversal Modes in Multisegmented Nanowire Arrays with Long Aspect Ratio - Allende-Prieto, S (American Institute of Physics, 2015)
A detailed numerical analysis of the magnetization reversal processes in multisegmented nanowire arrays was developed. The nanowires have a long aspect ratio and are formed by magnetic and non-magnetic sections alternately arranged in such a way that the array resembles magnetic layers separated by non-magnetic layers. Attention has been focused on the influence of magnetostatic interaction in the magnetic pattern formation of these magnetic nanostructures. Results from a magnetic correlation function among layers show that three different reversal modes can be detected depending on the number and distance between the magnetic segments. As a consequence of the different reversal modes, a non-monotonic behavior of the annihilation field in function of the distance between the layers is evidenced. Thus, these results are important for the production of magnetic devices with multisegmented nanowire arrays. © 2015 AIP Publishing LLC.